Effect Of Feeding Sweet Potato Vine-Based Diets as Partial Milk Substitutes for Dairy Calves in Uganda - Taabu, H.L.; Ndyomugyenyi, E.K.; Mutetikka, D.; Ebong, C. (Livestock Research for Rural Development, 2016)
A study was conducted to determine the potential of sweet potato vine-based diets as partial milk substitute (PMS) for dairy calves. Twenty five Friesian bull-calves weighing 38.7 ± 4.56 kg were fed composite meals containing 0, 30, 40, 50 and 60% air-dried sweet potato vines (SPV) as partial milk substitutes in a completely randomized design (CRD) over a seventy day period. Dietary treatments were introduced 15 days after calving. Milk offered was reduced by one litre every fortnight until 70 days after birth. Proximate and mineral analyses were carried out for ingredients and dietary treatments. Feed intake (FI), average daily weight gains (ADG), feed: gain ratio and variable cost per unit of gain were computed over the experimental period.
Keywords: calving, energy intake, livestock, milk replacers, replacement stock, variable cost